2012
DOI: 10.1097/mph.0b013e31824435a1
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Allogeneic Hematopoietic Stem Cell Transplants Without Total Body Irradiation in Pediatric Patients With Acute Lymphoblastic Leukemia

Abstract: The most widely accepted conditioning regimen to allogeneic hematopoietic stem cell transplantation consists of total body irradiation, especially in patients affected by acute lymphoblastic leukemia (ALL). In this retrospective study, we report our experience on hematopoietic stem cell transplantation in 44 pediatric patients with acute lymphoblastic leukemia using a non-radiation-based conditioning regimen (busulfan/cyclophosphamide). Median age at transplantation was 12.5 years (range, 4 to 14 y). 39 out of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…25 One of the major regimen-related toxicities and complications is related to TBI-based preparative regimens 26 that have recently been removed from conditioning regimens due to lower TRM and better quality of life. [27][28][29] In this study, we evaluated our long-term follow-up of pediatric AML patients who underwent HSCT without the use of TBI regimen. We had a high rate of matched sibling donor compared with other studies that is because of high Although several studies did not find sex as significant prognostic factor in AML patients, some studies reported that female patients might do slightly better than male patients.…”
Section: Discussionmentioning
confidence: 99%
“…25 One of the major regimen-related toxicities and complications is related to TBI-based preparative regimens 26 that have recently been removed from conditioning regimens due to lower TRM and better quality of life. [27][28][29] In this study, we evaluated our long-term follow-up of pediatric AML patients who underwent HSCT without the use of TBI regimen. We had a high rate of matched sibling donor compared with other studies that is because of high Although several studies did not find sex as significant prognostic factor in AML patients, some studies reported that female patients might do slightly better than male patients.…”
Section: Discussionmentioning
confidence: 99%
“…We were not able to identify risk factors for engraftment failure because of the low number of patients. The median time to neutrophil recovery for the patients with engraftment was 13 days (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The median time to platelet engraftment was 10 days (8-70), and the median times to platelet counts of 50 × 10 9 /L and 100 × 10 9 /L were 13 days (9-150) and 15 days (9-150), respectively.…”
Section: Engraftment Kinetics and Supportive Carementioning
confidence: 98%
“…Moreover, TBI-based regimens are associated with more transplant-related toxicity and more late effects, especially in low-weight pediatric patients. Non-radiation-based preparative regimens can be used in pediatric patients with high-risk acute leukemia 12 and fludarabine-based reduced-intensity conditioning regimens are safe and effective alternatives to TBI in HSCT. An important observation in this study was the fact that the conditioning regimen was well tolerated, with a low incidence of severe complications, similar to that of recently published reports.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil engraftment was defined as an ANC >0.510 9 /L for 3 consecutive days after HSCT without growth factor support. Platelet engraftment was defined as a platelet count >20 × 10 9 /L for 3 consecutive days after HSCT without transfusion support for 7 d .…”
Section: Methodsmentioning
confidence: 99%